Determinan Pilihan Karir Mahasiswa Fakultas Kedokteran sebagai Spesialis di Indonesia - Rizma Adlia Syakurah; Dwi Atika Sari; Dendy Riansyah; Priska Yolanda (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: In this “Jaminan Kesehatan Nasional” (JKN) era, career preference among medical students became an important issue to be concerned with, especially regarding career as a specialist physician in order to ensure equal distribution of doctor's quantity and profession variation. Several studies had been conducted abroad with aim to analyse career preference's determinants of medical students, but these kind of studies are rarely found in Indonesia. The objective of this study is to analyse the determinants of career preferences in medical speciality among medical students in Indonesia.Method: Cross-sectional study with questionnaire. Population of the study were first year students in 13 public universities with “A” accreditation. Samples collected by stratified consecutive sampling method. Chi square was used to evaluate the association between career preferences with socio-demographic and academic factors.Results: Among 315 samples, 83,8% students chose medical speciality as their preferred career. Determinants which influence career preferences are having parents that works in medical field (P= 0.036), higher parents earning (P= 0.04), and deciding to enrol to medical school since before high school (P= 0.036).Conclusion: Parents social economic state and background, along with personal motivation are some of important determinants to be considered. More studies need to be conducted in this area, especially regarding the underlying behaviour that affect further career preferences. Socialization about the importance and merits of other medical professions needs to be implement to prevent gap in medical profession's distribution later on.